The prevalence of occult ovarian cancer in the series of 155 consequently operated high risk asymptomatic patients - Gornjec, Andreja (Radiology and oncology (Ljubljana), 2020)
We assessed the prevalence, localization, type and outcome of occult cancer at risk-reducing salpingo-oophorectomy or salpingectomy (RRSO) in asymptomatic carriers of pathogenic or likely pathogenic BRCA1/2 variants and high-risk BRCA1/2 negative women. Patients and methods. A retrospective analysis of all consecutive gynaecologic preventive surgeries from January 2009 to December 2015 was performed. Participants underwent genetic counselling and BRCA1/2 testing before the procedure. Data on clinical parameters, adjuvant treatment and follow-up were collected and analysed. Results. One hundred and fifty-five RRSO were performed in 110 BRCA1, 35 BRCA2 carriers of pathogenic or likely pathogenic variants and 10 high-risk BRCA1/2 negative women, at the mean age of 48.3 years. Nine occult cancers (9/155, 5.8%) were identified; eight in BRCA1 positive women and one in high-risk BRCA1/2 negative woman. We identified four non-invasive serous intraepithelial tubal carcinomas (3 in BRCA1 carriers and 1 in a high-risk BRCA1/2 negative woman) and five invasive tubo-ovarian high grade serous cancers (all detected in BRCA1 carriers). Only one out of nine patients (11.1%) with occult cancer had a slightly elevated CA-125 value preoperatively. Conclusions. A 5.8% prevalence of occult invasive and noninvasive tubo-ovarian serous cancer after RRSO was found in high risk asymptomatic and screen negative women. We conclude that RRSO should be performed in BRCA1/2 carriers and in high-risk BRCA1/2 negative women. Age of preventive gynaecologic surgery should be carefully planned, taking into account the completion of childbearing age and type of mutation. The results favour the tubal hypothesis of tubal origin of high grade serous ovarian and peritoneal cancer. Cytology result of peritoneal cavity washing was important for the decision making process in determining treatment. Cytology examination should be performed in all cases of RRSO. CA-125 assay did not prove to be an effective screening tool for early cancer detection in our patients.
Keywords: jajčniki; karcinom; prevalenca; preventivna medicina; rak (medicina)